Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12877-023-03983-2
|View full text |Cite
|
Sign up to set email alerts
|

Sleep movements and respiratory coupling as a biobehavioral metric for early Alzheimer’s disease in independently dwelling adults

Abstract: Introduction Sleep disorder is often the first symptom of age-related cognitive decline associated with Alzheimer’s disease (AD) observed in primary care. The relationship between sleep and early AD was examined using a patented sleep mattress designed to record respiration and high frequency movement arousals. A machine learning algorithm was developed to classify sleep features associated with early AD. Method Community-dwelling older adults (N =… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Latency between movement arousals and coupled respiratory upregulation derived from the sleep monitoring produced >85% sensitivity and specificity. 30 As with other measures, collecting sleep data at home provides opportunities for additional evaluation of variability and change over time at a minimal cost and engagement. At‐home passive sleep monitoring via infrared sensors has suggested that tracking sleep through movement and sleep time could be an effective method for detecting dementia.…”
Section: Active and Passive Ad Monitoring In Resea...mentioning
confidence: 99%
“…Latency between movement arousals and coupled respiratory upregulation derived from the sleep monitoring produced >85% sensitivity and specificity. 30 As with other measures, collecting sleep data at home provides opportunities for additional evaluation of variability and change over time at a minimal cost and engagement. At‐home passive sleep monitoring via infrared sensors has suggested that tracking sleep through movement and sleep time could be an effective method for detecting dementia.…”
Section: Active and Passive Ad Monitoring In Resea...mentioning
confidence: 99%
“…Changes in mood, disturbed sleep patterns, and memory loss are among the earliest symptoms of AD. Although AD primarily affects the brain, during the course of the disease, extracranial body systems can be affected, including the respiratory system [ 61 ], digestive system [ 62 ], and urinary system [ 63 ] as well as changes in the epidermal layer of the skin [ 64 ]. Considering these and other organ-related symptoms, AD is increasingly being recognized as a multi-organ disorder [ 65 ].…”
Section: Introductionmentioning
confidence: 99%